2022
DOI: 10.3390/s22145372
|View full text |Cite
|
Sign up to set email alerts
|

Tunable White Light for Elders (TWLITE): A Protocol Demonstrating Feasibility and Acceptability for Deployment, Remote Data Collection, and Analysis of a Home-Based Lighting Intervention in Older Adults

Abstract: Sleep disturbances are common in older adults and may contribute to disease progression in certain populations (e.g., Alzheimer’s disease). Light therapy is a simple and cost-effective intervention to improve sleep. Primary barriers to light therapy are: (1) poor acceptability of the use of devices, and (2) inflexibility of current devices to deliver beyond a fixed light spectrum and throughout the entirety of the day. However, dynamic, tunable lighting integrated into the native home lighting system can poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The present study is an extension of the previous Tunable White LIghT for Elders (TWLITE) study [14]. In TWLITE, participants homes were retrofitted with a tunable lighting system that was remotely controlled, such that all emitted light mirrored their natural environment according to time of day.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study is an extension of the previous Tunable White LIghT for Elders (TWLITE) study [14]. In TWLITE, participants homes were retrofitted with a tunable lighting system that was remotely controlled, such that all emitted light mirrored their natural environment according to time of day.…”
Section: Overviewmentioning
confidence: 99%
“…Pressure-sensitive bed mats placed under the mattress (EmFit Corp., San Marcos, TX, USA) were used to record information about the patterns of study participants time in bed. These bed mats were previously validated against wrist-based actigraphy [11,15] as well as the PIR motion sensor network [14] to identify sleep; however, henceforth, "time in bed" will be retained as the primary bed mat-related outcome. Figure 2 shows the nightly time in bed for three representative study participants as measured using the EmFit bed mats.…”
Section: Time In Bedmentioning
confidence: 99%
See 1 more Smart Citation
“…St-Jean et al found that the utilization of blue-rich light enables older individuals to engage in more activities, despite the common perception that blue light diminishes work efficiency [10]. Furthermore, research has expanded to encompass more specific indicators of indoor lighting, such as illumination [11][12][13][14], color temperature [15][16][17], and light source location [18]. Research studies have shown that while illumination has minimal impact on the physiological rhythms of the elderly, it significantly influences their psychological state.…”
Section: Introduction 1the Difference In Visual Environment Acceptanc...mentioning
confidence: 99%